KETERSEDIAAN SARANA DAN PRASARANA UNTUK MENUNJANG KEGIATAN PENDIDIKAN SEKOLAH DASAR - Muhammad Alfalah; Muhammad Zakaria; Siti Rofingah; Amelia Assahra; Mardion Al Mahdi (STKIP Pesisir Selatan, 2025)
The availability of school facilities and infrastructure is a key factor in supporting the effectiveness of educational activities. This study aims to analyze the level of readiness of school facilities, particularly related to classrooms and learning technology devices such as anyboards, in supporting the teaching and learning process. The research method used was a qualitative descriptive approach through direct observation, interviews with educators, and document studies related to mapping educational facility needs. The results show that most schools still face significant obstacles in the form of limited adequate classroom space. This condition results in alternating classroom use and impacts the effectiveness of learning time. Furthermore, the lack of modern learning technology devices, including anyboards, hinders the implementation of interactive and digital learning strategies that should increase student participation and understanding. These findings emphasize the need for more optimal planning for the procurement of facilities and infrastructure, including the construction of additional classrooms and the provision of technology devices relevant to current learning needs. This research is expected to serve as a reference for policymakers in developing programs to continuously improve the quality of educational facilities.